2016
DOI: 10.1017/cem.2016.27
|View full text |Cite
|
Sign up to set email alerts
|

A national survey of Canadian emergency medicine residents’ comfort with geriatric emergency medicine

Abstract: Background: Geriatric patients represent a large and complex subgroup seen in emergency departments (EDs). Competencies in geriatric emergency medicine (EM) training have been established. Our objectives were to examine Canadian postgraduate year (PGY)-5 EM residents' comfort with the geriatric EM competency domains, assess whether Canadian EM residents become more comfortable through residency, and determine whether geriatric educational exposures are correlated with resident comfort with geriatric EM. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…This finding is in line with previous studies addressing the value of putting geriatricians at the “front door” of the hospital; it allows early specialist review, reduces the undertaking of multiple similar patient assessments by medical staff and improves the timeliness and appropriateness of ED disposition decisions [48]. Literature shows that many ED physicians and nurses are not well-trained in geriatric emergency medicine and feel less comfortable when dealing with older adults [49, 50]. Consequently, the management of older adults in the ED often requires more time and resources compared to younger adults [51].…”
Section: Discussionsupporting
confidence: 87%
“…This finding is in line with previous studies addressing the value of putting geriatricians at the “front door” of the hospital; it allows early specialist review, reduces the undertaking of multiple similar patient assessments by medical staff and improves the timeliness and appropriateness of ED disposition decisions [48]. Literature shows that many ED physicians and nurses are not well-trained in geriatric emergency medicine and feel less comfortable when dealing with older adults [49, 50]. Consequently, the management of older adults in the ED often requires more time and resources compared to younger adults [51].…”
Section: Discussionsupporting
confidence: 87%
“…Understanding the diagnostic accuracy of ultrabrief dementia screening instruments is also relevant for medical educators. Approximately one‐third of senior emergency medicine residents lack confidence in the recognition and management of cognitive disorders, despite the emphasis on assessing for dementia and delirium as a core competency by the American Board of Emergency Medicine in 2010 . Evidence‐based educators should emphasize that not all dementia screening instruments are equally accurate—and that none of them is diagnostic to rule in dementia.…”
Section: Discussionmentioning
confidence: 99%
“…However, ED professionals have historically not had specific training or been provided with guidelines for the care of frail older people . Several studies have reported that ED professionals feel unconfident in dealing with complex older patients, which may be related to the underrepresentation of older patient care issues in the medical and nursing curricula . Surveys by the American College of Emergency Physicians (ACEP) found that practicing EPs considered it more difficult to manage older adults compared to younger counterparts and that the time spent during residency training on geriatric emergency medicine (GEM) was inadequate .…”
mentioning
confidence: 99%